Finnish norms for young children on the Strengths and Difficulties Questionnaire. (October 2014) - Borg, Anne-Mari; Kaukonen, Pälvi; Joukamaa, Matti; Tamminen, Tuula
Abstract Background: Early recognition of children's mental health problems is crucial. Although the Strengths and Difficulties Questionnaire (SDQ) is a commonly used screening method, further research is needed on its validity and norms for young children. Aims: The aims of the study were to confirm the adjusted lower (normal/borderline) and upper (borderline/abnormal) cut-offs for the SDQ in a Finnish community sample of 4–9-year-old children, and to explore the SDQ's ability to identify the children with mental health problems. Methods: Parents and teachers completed the SDQs (n = 2666). The Development and Well-Being Assessment (DAWBA) was administered to parents and teachers of 646 children. Results: The overall participation rate was 57%. The suggested cut-offs for the SDQ total difficulties scale rated by parents and teachers were 2–5 points lower than the corresponding published British norms. The sensitivity for the total score normal/borderline cut-off (9/10) was 76% in the parent and 66% in the teacher reports and for the borderline/abnormal cut-off (11/12) 90% and 70% respectively. The respective specificity values were 69%, 63%, 74% and 66%. The area under curve (AUC) values of the higher cut-offs were good for parent (0.87) and satisfactory for teacher rated (0.76) total scores. The presence of a DAWBA-rater assigned diagnosis in the abnormal group compared with the normal group was sixfold in the parent and threefold in the teacher reported SDQs. Conclusions: The suggested cut-offs were clearly lower than the British norms. Yet the properties of the method's discriminative validity were acceptable. Population specific norms, taking into account both the culture and children's age, seem necessary for screening and for international comparisons of the method's validity properties.